A Review of the Health Burden Associated with Air Pollution Exposure in Nepal - Joshi, Prayag Raj; Khadka, Kalpana; Karki, Tej Bahadur (NPRC Journal of Multidisciplinary Research, 2026)
Background: Air pollution has emerged as the foremost environmental challenge threatening public health in Nepal, particularly within the rapidly growing population of the Kathmandu Valley. The region consistently experiences hazardous air quality, with pollutants from vehicular emissions, industrial activities, brick kilns, and household biomass combustion exceeding World Health Organization (WHO) safe limits.Objective: This study aims to synthesize the existing evidence on air pollution’s health impacts in the Kathmandu Valley, identify critical gaps in current research, and evaluate the efficacy of policy enforcement to propose comprehensive, multi-sectoral solutions.Methods: This review synthesizes findings from existing literature on environmental health, epidemiological data, and policy analysis related to air quality management in Nepal. It focuses on the intersection of pollution sources, clinical health outcomes, and the vulnerabilities of specific subpopulations.ResultsThe analysis confirms a direct correlation between air pollution and elevated rates of respiratory diseases (including asthma, chronic obstructive pulmonary disease, and pneumonia) as well as cardiovascular disorders (such as hypertension and ischemic heart disease). Vulnerable groups—namely children, pregnant women, and the elderly—are disproportionately affected. However, significant research gaps persist, including a lack of long-term exposure data, limited comprehensive clinical evaluations, an over-reliance on short-term monitoring and self-reported health data, and insufficient investigation into cumulative health impacts and non-respiratory conditions. These gaps are compounded by weak policy enforcement, which undermines national air quality improvement goals.ConclusionAddressing Nepal’s air quality crisis requires an integrated approach that moves beyond fragmented interventions. The government must prioritize strengthening regulations on pollution sources, increasing investment in longitudinal scientific research, and developing targeted community-based programs.ImplicationsSustainable progress necessitates the adoption of green infrastructure, clean energy solutions, and cleaner transportation systems. Public awareness campaigns, coupled with specific protective measures for vulnerable groups, are essential for achieving health equity. A coordinated, multi-sectoral strategy—unifying policy reform, rigorous scientific inquiry, and active community participation—is critical to safeguarding public health and ensuring long-term environmental sustainability in Nepal.